Quick hits for teaching with technology [ successful strategies by award-winning teachers - Morgan, Robin K. , 1961-; Olivares, Kimberly T. (Bloomington, Indiana : Indiana University Press, 2012)
"How should I use technology in my courses? What impact does technology have on student learning? Is distance learning effective? Should I give online tests and, if so, how can I be sure of the integrity of the students' work? These are some of the questions that instructors raise as technology becomes an integral part of the educational experience. In Quick Hits for Teaching with Technology, award-winning instructors representing a wide range of academic disciplines describe their strategies for employing technology to achieve learning objectives. They include tips on using just-in-time teaching, wikis, clickers, YouTube, blogging, and GIS, to name just a few."--book cover
1. Promoting engagement -- 2. Providing access -- 3. Enhancing evaluation -- 4. Becoming more efficient
Includes bibliographical references (p. [111]-114) and index
Keywords: Educational technology; Learning